The Study of Nutritional Requirements and Physiological Changes in Space Station - V. Sabeetha; A. Lokeshwari (International Journal of Nutritions, 2024)
This article focuses on the impact of physiological adaptations to weightlessness on nutrient and food requirements in space. These modifications entail reductions in body water and plasma volume, which affect the cardiovascular and renal systems. Spaceflight poses intricate and predominantly detrimental effects on the human body, spanning both short and long durations. Long-term weightlessness leads to significant issues like muscle atrophy, skeletal deterioration, cardiovascular function deceleration, reduced red blood cell production (space anemia), balance and eyesight disorders, immune system alterations, fluid redistribution causing a "moon-face" appearance, body mass loss, nasal congestion, sleep disturbances, and excessive flatulence. Research on engineering challenges for space travel and propulsion systems dates back a century, with recent emphasis on understanding how humans can endure extended space missions. November 2019 findings highlighted serious blood flow and clot problems in astronauts during a six-month study on the International Space Station. Challenges in mitigating hazards like weightlessness, characterized as a microgravity environment, involve addressing proprioception loss, fluid distribution changes, and musculoskeletal system deterioration. Additionally, changes in bone mass contribute to the increased risk of forming renal stones due to higher urinary calcium concentrations. There are several aspects of nutrition in space, including providing essential nutrients and maintaining the health of the immune, musculoskeletal, and endocrine systems. Furthermore, a thorough analysis is conducted on the effects of environmental elements such as radiation, temperature fluctuations, and atmospheric pressures on nutrition in space. Precisely calculating the nutritional amounts required to maintain health and mitigate the effects of microgravity is essential, especially for long-term space missions.
Keywords: Metabolism; Muscle Mass; Nutrition in Space; Physiological Changes; Space Station